ANALISIS EFEKTIVITAS ENDOMIKORIZA DAN AMELIORAN TERHADAP PEMBENTUKAN JARINGAN KAYU SEMAI JABON MERAH (Anthochepalus macropyllus) - ceng asmarahman (Forestry Study Program University Of Mataram, 2023)
Arbuscular mycorrhizal fungi (FMA) is a potential microbial that can increase plant growth in various conditions of planting media, including in post-mining soil limestone. In the post-mining land, limestone has been found several types of FMA. This type of FMA has the potential as an inoculant source that is thought to increase the growth of the red jabon plant (anthocephalus macropyllus). Furthermore PT. Holcim Indonesia Tbk also produces the remaining cement laundering waste (LPS), which has the potential as ameliorating material that can increase the availability of nutrition, improve soil aggregate and increase the growth and formation of plant tissue (xylem). Considering that similar research is still minimal, it is necessary to research the effectiveness of using FMA inoculants and Amelioran material on the growth and formation of Red Jabon Semai Wood (A. Macropyllus) in the post-mining soil media. The varied analysis of variables using SPSS software version 10.01 was to determine the effect of treatment and the combination of treatment of the measured variables. At the same time, the analysis of wood anatomy uses the Sass method. The results showed that FMA and Amelioran soil effectively increased the growth and formation of wood networks in A. Macrophyllus. The interaction of FMA and LPS treatment can increase the proportion of phloem and xylem and is significant in increasing the proportion of empul. In contrast, the single FMA treatment effectively increases the growth of the proportion of phloem and xylem. Percentage of Increasing Floem Network Proposi M1 Treatment (64.91%), M2 (66.12%), and Increased Xylem Network Composition for M1 Treatment (16.59%) and M2 (16.38%).